Discovery of key biomarkers in tourette syndrome by network pharmacology - Zhao, Jiali; Bai, Xiaohong (Frontiers in Pharmacology, 2024)
Background Yangxue Xifeng Decoction (YXD) has been utilized in clinical settings for the treatment of Tourette Syndrome (TS). However, the action mechanism of YXD needs further research. Methods The ingredients and targets of YXD were identified via database searches and then constructed an active ingredient-target network using Cytoscape. Pathway enrichment analysis was performed via Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). The core genes were determined by LASSO regression and SVM algorithm. Additionally, we analyzed the immune infiltration. The signaling pathways associated with core genes were investigated through KEGG and GO. We predicted the transcription factors using “RcisTarge”. Results 127 active ingredients of YXD and 255 targets were obtained. TNF and the IL-17 signaling pathway were the main pathways. OPRM1 and VIM were screened out as core genes, which were associated with the immune infiltration. The signaling pathways involved in OPRM1 and VIM were enriched. Furthermore, remarkable correlation was found between OPRM1 and VIM levels and other TS-related genes such as MAPT and MAPT. Conclusion OPRM1 and MAPT, and the signaling pathways are associated with TS. YXD exerts its therapeutic TS through multi-component and multi-targets including immune infiltration.